ASPEK MISE EN SCENE DALAM MENGGAMBARKAN PERUBAHAN PERILAKU TOKOH MARIA PADA FILM LOOK AWAY - GEMMA IRSYADIL IBAD; wajihudin wajihudin; Didik Suharijadi (ROLLING, 2023)
This study discusses mise-en-scene in describing changes in the behavior of Maria's characters in the film Look Away. The study was conducted to describe the behavior and behavior changes of Maria's characters in the film Look Away through the mise-en-scene aspect. The research data was examined using the theory of mise-en-scene and psychoanalysis Sigmund freud. Psychoanalysis Sigmund Freud was used to analyze behavior and changes in Maria's character behavior, while mise-en-scene was used to analyze visual aspects in describing changes in Maria's character's behavior in the Look Away movie. This study uses a type of qualitative research using descriptive methods. Based on the research that has been done, it is known that Maria is the main character who is kind and shy, while the figure of Airam is a supporting figure as well as an antagonist who has a bad character, and is the mastermind of the occurrence of all conflicts in the story in Look Away. Mise-en-scene elements such as settings, costumes and make-up, as well as players and movements are able to describe changes in Maria's character's behavior as a shy person who becomes a character who looks evil and gives a scary impression to friends who often make Maria worse.